2008
DOI: 10.1007/s10509-008-9736-4
|View full text |Cite
|
Sign up to set email alerts
|

Energy of the universe in Bianchi-type I models in Møller’s tetrad theory of gravity

Abstract: Abstract. In this paper, using the energy definition in Møller's tetrad theory of gravity we calculate the total energy of the universe in Bianchi-type I cosmological models which includes both the matter and gravitational fields. The total energy is found to be zero and this result agrees with a previous works of Banerjee-Sen who investigated this problem using the general relativity version of the Einstein energy-momentum complex and Xulu who investigated same problem using the general relativity versions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(22 reference statements)
1
0
0
Order By: Relevance
“…If we solve total energy-momentum definitions for N -dimensional Bianchi type I universe in GR and TG, we found that all energy and momentum definitions have vanished because the energy contributions from gravitational field and the matter inside an arbitrary two-surface cancel each other [11], also we could say that GR and TG are equivalent theories. These results agree with [50][51][52]24]. Also these are seen in Tables 3 and 4.…”
Section: -12supporting
confidence: 89%
“…If we solve total energy-momentum definitions for N -dimensional Bianchi type I universe in GR and TG, we found that all energy and momentum definitions have vanished because the energy contributions from gravitational field and the matter inside an arbitrary two-surface cancel each other [11], also we could say that GR and TG are equivalent theories. These results agree with [50][51][52]24]. Also these are seen in Tables 3 and 4.…”
Section: -12supporting
confidence: 89%